The Effect of Argument-Driven Inquiry on Students’ Scientific Reasoning and Argumentation Skills - Ielda Paramita; Nurul Kami Sani; Syamsuriwal Syamsuriwal; Rudi Santoso; Indo Tang (Jurnal Studi Guru dan Pembelajaran, 2025)
Developing students’ scientific reasoning and argumentation skills is essential for achieving meaningful learning in physics, as these competencies are fundamental to scientific literacy and higher-order thinking. Nevertheless, physics instruction in many secondary classrooms still prioritizes procedural problem solving, providing limited opportunities for students to engage in reasoning and scientific discourse. This condition highlights the urgent need for instructional models that explicitly integrate inquiry and argumentation into learning. This study examined the effect of the Argument-Driven Inquiry (ADI) model on students’ scientific reasoning and argumentation skills using a mixed-method quasi-experimental design with a non-equivalent pretest–posttest control group. The participants were 72 eleventh-grade science students from a public senior high school in Central Sulawesi, Indonesia, divided into an experimental (ADI) and a control (conventional instruction) group. Data were collected using validated reasoning and argumentation instruments and analyzed through normalized gain, ANCOVA, and discourse analysis. The results showed that students in the ADI group achieved higher improvements in scientific reasoning (N-gain = 0.66, high) and argumentation quality (N-gain = 0.72, high) than those in the control group. Discourse analysis further revealed more frequent construction of claims, use of evidence, and rebuttals among ADI students, indicating deeper epistemic engagement. In conclusion, this study provides novel empirical evidence that ADI effectively strengthens reasoning-based physics learning by simultaneously enhancing students’ scientific reasoning and argumentation, offering a robust pedagogical contribution for fostering higher-order thinking in secondary science education.